Location, location, location: A comparison of student experience in a lecture hall to a small classroom using similar techniques. (July 2019) - Bolden, Edward C; Oestreich, Tina M; Kenney, Michael J; Yuhnke, Brian T
This article focuses on students' perceptions of small-group activities, discussion, and technology-based interactivity implemented in two different learning environments, namely, in a large, traditional lecture hall and in a smaller classroom. The Engaged Learning Index, developed by Schreiner and Louis, was used along with several items to determine student perceptions of the activities that they had been asked to undertake. This followed a faculty training program designed to help faculty to use discussion, technology, and small-group work to enhance student engagement. Students in a course in which faculty taught in a traditional lecture hall (in an auditorium) were compared with students who had content and material delivered within a small classroom. Data indicated more active engagement in courses hosted in small classrooms, with slightly higher ratings on meaningful processing and active participation, while students in the course run by faculty in the traditional lecture hall reported a deeper processing of material, more advanced learning, more focused attention, and a better understanding overall. An explanation of potential differences is provided.